2014
DOI: 10.1016/j.ijrobp.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Magnetic Resonance Spectroscopic Imaging at 3 Tesla for Early Response Assessment of Glioblastoma Patients During External Beam Radiation Therapy

Abstract: Purpose To evaluate the utility of 3D-MR proton spectroscopic imaging for treatment planning and its implications for early response assessment in glioblastoma multiforme. Methods and Materials Eighteen patients with newly diagnosed, histologically confirmed glioblastoma had 3D-MR proton spectroscopic imaging (MRSI) along with T2 and T1 gadolinium enhanced MR images at simulation and at boost treatment planning after 17-20 fractions of radiotherapy. All patients received standard radiotherapy with temozolomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…8,9 The results of the quantitative analysis suggest that metabolic parameters at baseline, one month, and 2 months into treatment were able to capture alterations in tumor burden associated with these effects. The findings are consistent with prior studies using MRSI data to predict response to therapy, [20][21][22] suggesting that it may be helpful for providing an early assessment of the utility of other combination therapies. Previous studies have evaluated the relationship of anatomic imaging parameters to outcome for patients with newly diagnosed GBM receiving standard-of-care treatment with RT and temozolomide.…”
Section: Discussionsupporting
confidence: 89%
“…8,9 The results of the quantitative analysis suggest that metabolic parameters at baseline, one month, and 2 months into treatment were able to capture alterations in tumor burden associated with these effects. The findings are consistent with prior studies using MRSI data to predict response to therapy, [20][21][22] suggesting that it may be helpful for providing an early assessment of the utility of other combination therapies. Previous studies have evaluated the relationship of anatomic imaging parameters to outcome for patients with newly diagnosed GBM receiving standard-of-care treatment with RT and temozolomide.…”
Section: Discussionsupporting
confidence: 89%
“…Both 1 H MRS [5] and [ 11 C]-choline-PET [6] imaging are finding important roles in monitoring response to radiation treatment in patients with glioblastoma multiforme [5] and in detecting recurrence in patients with prostate cancer [6]. Increasingly, radiation oncologists are incorporating these imaging modalities in restaging and assessment of response in these patients [5,6].…”
Section: Cancer Detection and Monitoring Response To Treatmentmentioning
confidence: 99%
“…Increasingly, radiation oncologists are incorporating these imaging modalities in restaging and assessment of response in these patients [5,6]. A recent study demonstrated that [ 11 C]-choline-PET/CT positive lung tumors also contained high expression levels of choline acetyltransferase and Chk-α [112].…”
Section: Cancer Detection and Monitoring Response To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the early change of the Cho-to-NAA index during RT has been shown to predict early progression within an observational study of GBM where the voxel-based analysis of 3D MRSI data retrospectively revealed a significant increase in median Cho/NAA in the group of patients with early recurrent tumour. 79 Alongside with the metabolites mentioned above, there is another promising MRSI approach examining lactate (Lac) accumulation as a surrogate for hypoxic and subsequently radioresistant areas that has also shown the potential to predict local recurrence. Therefore, lactate imaging might also serve as a biological targeting or dose-painting technique.…”
Section: Imaging Implications In Neurosurgerymentioning
confidence: 99%